Sociodemographic determinants of telehealth utilisation in general practice during the COVID‐19 pandemic in Australia - Dai, Zhaoli; Sezgin, Gorkem; Hardie, Rae‐Anne; McGuire, Precious; Pearce, Christopher; McLeod, Adam; Georgiou, Andrew (Internal medicine journal, 2023)
This analysis assessed the sociodemographic characteristics of telehealth utilisation during the coronavirus disease 2019 (COVID‐19) pandemic from March 2020 to August 2021 in Australia. Drawing on 860 general practice providers among 3 161 868 patients, 24 527 274 consultations were recorded. Telehealth accounted for 37.6% of the consultations, with 2.4% through videoconferencing and 35.2% through phone consultations. Our multivariate regression analyses indicated low utilisation of videoconferencing compared with phone consultations among older adults, those living in rural communities and migrants from non‐English speaking countries.